Developing Modelling-Based Speaking Module for Informal Interaction to Support Independent Learning of Speaking Skill - Ratih Laily Nurjanah; Deswandito Dwi Saptanto; Maya Kurnia Dewi (ELT-Lectura, 2021)
The lack of English module in speaking skill to support the teaching and learning process becomes one of the reasons for this study to come up. Another one is the reality that now, students are expected to be able to develop themselves independently without being dependent on lecturers since the Ministry of Education issued a new curriculum of Kampus Merdeka (Independent Campus). This is such an extended period from what is being faced by the world during outbreak era where classroom activities cannot be held. This study aims to observe what kind of speaking module is needed by students and to develop a modelling-based speaking module in informal interaction to support the independent learning process. This is a research and Development method according to Borg and Gall theory with 10 steps of development. The results show students need a module that can give them examples how to pronounce words but not in form of phonetic transcription. A module is then developed containing various daily expressions accompanied by an USB flash-drive contains recordings of a native speaker giving examples or models on how to pronounce the expressions accurately. Student are expected to be able to imitate the examples whenever they need until they can produce correct pronunciation and intonation.